ANALISIS PENGARUH GAYA KEPEMIMPINAN, KOMUNIKASI, DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. INDOPURA UTAMA TANJUNG MORAWA KAB. DELI SERDANG - Simbolon, Adrian Babtissay; Simbolon, Sahat; Simbolon, Yulia Kristina (UNIKA Santo Thomas, 2025)
This study aims to examine the influence of leadership style, communication, and work environment on employee job satisfaction at PT. Indopura Utama Tanjung Morawa Kab. Deli Serdang over a three-month period, from March to May 2022. The method used was a census technique, with all 70 employees serving as the research sample. Data were collected through a questionnaire measuring the variables of leadership style, communication, work environment, and employee job satisfaction. The data analysis included validity and reliability tests, descriptive analysis, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression, correlation test, t-test, F-test, and coefficient of determination test. The descriptive analysis results showed that the variables of leadership style, communication, work environment, and job satisfaction were categorized as good. Based on the partial hypothesis testing (t-test), leadership style, communication, and work environment were found to have a positive and significant effect on employee job satisfaction. The coefficient of determination indicated that these three variables contributed 75.7% to job satisfaction, while the remaining 24.3% was influenced by other factors not examined in this study, such as compensation, work discipline, and motivation.